2008
DOI: 10.4018/jitwe.2008010103
|View full text |Cite
|
Sign up to set email alerts
|

Localized User Interface for Improving Cell phone Users' Device Competency

Abstract: This study tried to examine how cell phone users who undergo a technology leap acquire their procedural knowledge of operating a cell phone and to find out which factors can improve their device competency. Using interviews, usability tests, and a questionnaire, this study found out that many respondents use unstructured means such as asking other cell phone users or rote learning in gaining their procedural knowledge. Some factors influencing users’ device competencies that were found in this study are classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Usefulness: Participants of a study conducted by [16] on the localization of accounting software were of the opinion that localized software contributes to a better understanding of accounting concepts compared to a non-localized interface. In addition, a mixed approach study (usability tests using localized cell-phones interfaces, questionnaires, and interviews) of 88 participants revealed that localized software improves cell-phone users' device competency [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Usefulness: Participants of a study conducted by [16] on the localization of accounting software were of the opinion that localized software contributes to a better understanding of accounting concepts compared to a non-localized interface. In addition, a mixed approach study (usability tests using localized cell-phones interfaces, questionnaires, and interviews) of 88 participants revealed that localized software improves cell-phone users' device competency [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition based on studies [5,7,9] cultural background and user experience are also important factors to promote user understandings towards the design metaphors. In [7] the researchers came across with several users who perceive that an envelope is a function to transfer money based on the mental model that they built from previous experience using envelopes.…”
Section: Introductionmentioning
confidence: 99%
“…In [7] the researchers came across with several users who perceive that an envelope is a function to transfer money based on the mental model that they built from previous experience using envelopes. Another study by [4] design metaphors could provide an alternative user interface to user ability where they discovered users with low-level literacy would favor iconic user interface.…”
Section: Introductionmentioning
confidence: 99%